2011
DOI: 10.1128/aac.01780-10
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effect of a Triterpenoid Compound, with or without Alpha Interferon, on Hepatitis C Virus Infection

Abstract: A lack of patient response to alpha interferon (␣-IFN) plus ribavirin (RBV) treatment is a major problem in eliminating hepatitis C virus (HCV). We screened chemical libraries for compounds that enhanced cellular responses to ␣-IFN and identified a triterpenoid, toosendanin (TSN).Hepatitis C virus (HCV) is one of the most important pathogens causing acute and chronic hepatitis, liver cirrhosis, and hepatocellular malignancies (29). Alpha interferon (␣-IFN) combined with ribavirin (RBV) is the standard treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Previous studies have indicated that it is a selective presynaptic blocking agent (Shi et al ., ; Shi and Sun, ) and also effective in inhibiting botulism (Shi and Li, ; Shi and Wang, ). Additionally, it was demonstrated that TSN could inhibit hepatitis C virus infection by a marked suppression of HCV RNA replication (Watanabe et al ., ), and suppress proliferation of various human cancer cell lines (Shi and Tang, ; Zhang et al ., ). Therefore it may be a promising lead compound for treating botulism and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have indicated that it is a selective presynaptic blocking agent (Shi et al ., ; Shi and Sun, ) and also effective in inhibiting botulism (Shi and Li, ; Shi and Wang, ). Additionally, it was demonstrated that TSN could inhibit hepatitis C virus infection by a marked suppression of HCV RNA replication (Watanabe et al ., ), and suppress proliferation of various human cancer cell lines (Shi and Tang, ; Zhang et al ., ). Therefore it may be a promising lead compound for treating botulism and cancer.…”
Section: Introductionmentioning
confidence: 99%
“…CLZ is known to have pharmacological properties, including antibacterial, antivirus, anti‐neuraminidase, antioxidant, anticancer, anti‐inflammatory and analgesic activities (Liu et al, 2016; X.‐L. Tang et al, 2012; L. Wang et al, 2014; Watanabe et al, 2011; Xie et al, 2008; Xu, Yu, Wang, Xu, & Liu, 2018). However, it has been frequently reported to induce severe liver injury during clinical practice and empirical research in recent years (Yang et al, 2019; Yuen et al, 2010; J. Zheng et al, 2015), and liver cell necrosis was proven to be the main liver toxicity mechanism of CLZ (J. Zheng et al, 2015; Jie Zheng, Yu, Chen, Lu, & Fan, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, TSN suppressed proliferation and induced apoptosis of human cancer cells (Zhang et al, 2005) and displayed anti-botulinum and anti-microbial activities as well as antifeedant and insecticide properties (Carpinella et al, 2003; Shi and Wang, 2004; Kamau et al, 2016). TSN also inhibited hepatitis C virus infection by enhancing alpha interferon (Watanabe et al, 2011). Another MF compound, 28-deacetylsendanin, inhibited the replication of herpes simplex virus-1 (Kim et al, 1999).…”
Section: Introductionmentioning
confidence: 99%